Legal Protection of Pharmacists in Digital Prescription Services - Dwi Erawati, Ambar; Hargianti Dini Iswandari; Okti Tri Hastuti Dyah Retnaningrum; Lawrence Essuman (Arena Hukum, 2025)
This research examines the legal protections for pharmacists who provide drug services via digital prescriptions. Currently, no previous research discusses this issue. Prior studies have focused on the legal protection of patients and on electronic prescriptions as the legal object rather than on digital prescriptions. Schiff et al. (2018) examined the legal protection of patients as the legal object in electronic prescriptions, while Farghali et al. (2024) discussed e-prescribing to protect patients. Hareem et al. (2023) found that e-prescriptions can address technical problems in prescribing and guarantee patient safety. Departing from the above background, this research seeks to investigate the following problems: 1) What phenomenon arises in pharmacies that process digital prescription services? 2) Are pharmacists who process drugs on digital prescriptions legally protected? This study explains the phenomenon of digital prescription services and finds legal protection for pharmacists who process digital prescriptions. This research employs a qualitative phenomenology approach. Primary data consist of primary and secondary legal materials, which were analysed and concluded deductively. The theory of justice was used as the grand theory, while the legal system as the middle theory. This study found that there is a gap between the National Agency of Drug and Food Control (BPOM) Regulation Number 8 of 2020 concerning Drug and Food Control and the Indonesian Ministry of Health Number HK.01.07/MENKES/13/2023 concerning Professional Standards for Pharmacists. Electronic system technology is currently not ready in both technological and legal settings, as it cannot detect digital prescription validation, thereby failing to provide legal protection for pharmacists. For foreign readers, this research can serve as a reference for developing digital prescription technology, ensuring that digital prescriptions provide fair protection for patients and pharmacists.